Providing Schools with Enough Resources to Deliver Quality Education in the Philippines - World Bank Group (World Bank, Washington, DC, 2016)
Providing schools with direct funding to meet their operational needs is the cornerstone of the government's efforts to strengthen school-based management in the Philippines. Over the past five years, funds that the government has provided directly to schools to support their maintenance and other operating expenses have increased by 45 percent in real terms, demonstrating the government's commitment both to increasing operational funding and to providing schools with the funding that they need to implement their own improvement plans.